Representations Of Images Of “Third World Women” In Academy Award Winners For Best Picture From Postcolonial Feminism Perspective - Zhan, Xiaoling (2024)
This study analyses the construction of images of “Third World women” (TWW) in the cinematic medium by examining how these images function to produce and reproduce notions of difference about women and the “Third World”.